2021
DOI: 10.3389/fcell.2021.811666
|View full text |Cite
|
Sign up to set email alerts
|

Role of Exosomal Non-Coding RNAs in Bone-Related Diseases

Abstract: Bone-related diseases seriously affect the lives of patients and carry a heavy economic burden on society. Treatment methods cannot meet the diverse clinical needs of affected patients. Exosomes participate in the occurrence and development of many diseases through intercellular communication, including bone-related diseases. Studies have shown that exosomes can take-up and “package” non-coding RNAs and “deliver” them to recipient cells, thereby regulating the function of recipient cells. The exosomal non-codi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 197 publications
(200 reference statements)
0
14
0
Order By: Relevance
“…This finding led us to think that lncRNA-MALAT1 may be highly involved in the regulation of periodontitis-related physiological activities and the homeostasis in bone remodeling. Emerging studies showed that lncRNA is an essential active partner of osteogenic activity, 16 while the effect of lncRNA- OIP5-AS1, 17 Linc01133 18 and lncRNA-MALAT1 4 in osteogenic differentiation of osteoblasts and periodontal ligament stem cells have been reported. However, the role of lncRNA in osteoclastic differentiation has rarely been reported, while our results complemented the importance of lncRNA shuttled by osteoblasts exosome in bone remodeling, providing new possibilities for pathogenesis of periodontitis.…”
Section: Discussionmentioning
confidence: 99%
“…This finding led us to think that lncRNA-MALAT1 may be highly involved in the regulation of periodontitis-related physiological activities and the homeostasis in bone remodeling. Emerging studies showed that lncRNA is an essential active partner of osteogenic activity, 16 while the effect of lncRNA- OIP5-AS1, 17 Linc01133 18 and lncRNA-MALAT1 4 in osteogenic differentiation of osteoblasts and periodontal ligament stem cells have been reported. However, the role of lncRNA in osteoclastic differentiation has rarely been reported, while our results complemented the importance of lncRNA shuttled by osteoblasts exosome in bone remodeling, providing new possibilities for pathogenesis of periodontitis.…”
Section: Discussionmentioning
confidence: 99%
“…Exosomes with low molecular weight, small size, stable structure, less toxicity, and other characteristics are employed as “nano-medicine carriers” in tissue regeneration and/or disease treatment [ 100 , 101 ]. Importantly, ncRNAs are present in exosomes that perform diverse functions including bone remodeling and bone-related disease [ 102 ]. BMSCs, osteoclasts, osteoblasts, lymphocytes, and macrophages secrete exosomes that regulate bone metabolism [ 103 ].…”
Section: Exosomal Ncrnas and Bone Stem Cellsmentioning
confidence: 99%
“…In bone homeostasis, osteoblasts, osteoclasts, chondrocytes, and other cells secrete exosomal ncRNAs, which are involved in the regulation of bone-related diseases by inhibiting osteoclast differentiation, enhancing chondrocytosis, and promoting angiogenesis. Exosomal miRNAs secreted from MSCs exhibit potential regulatory effects on osteogenesis [ 102 ]. In humans, during BMSC osteogenic differentiation, the expression of exosomal miRNAs plays a regulatory role, and a low expression of miR-885-5p serves as a negative regulator by suppressing Wnt5 and RUNX2 [ 105 ].…”
Section: Exosomal Ncrnas and Bone Stem Cellsmentioning
confidence: 99%
See 2 more Smart Citations